THE USE OF CARTOON FILMS AS AUDIO-VISUAL AIDS TO TEACH ENGLISH VOCABULARY - Zulfadli A. Aziz; Rina Sulicha (Universitas Syiah Kuala, 2016)
The aims of this research are to study the use of cartoon films as an instructional media for teaching vocabulary to fifth grade students in an elementary school in Banda Aceh and to find out the responses of the students towards the use of this media. Two classes were taken as the sample, one as the control group (CG) and another as the experimental group (EG). Each group had 32 students. Data were collected through quantitative and qualitative methods. The quantitative data were the scores from the pre-tests and the post-tests of the students. The qualitative data were the questionnaire results used to identify the responses of the EG students to the use of cartoon films as an audio-visual aid in teaching vocabulary. The results from the quantitative data show that the mean of post-test scores of the EG is 94 whilst the mean of post-test scores of the CG is only 66. A comparison of the t-test score and the t-table score shows that the result of t-test is 2.35 whilst the result of t-table at a level of significance with α=0.05 and 95% probability is 1.67. This means that the score of t-testt-table, hence it could be concluded that the students who were taught by using cartoon films as an audio-visual aid got a better result than those who were taught by using other traditional visual aids. Furthermore, the responses from the students to the use of the cartoon film were highly positive. The use of cartoon films as an audio-visual media aid also resulted in a positive impact to the cognitive, affective, and psychomotor aspects of the students as it enhanced their vocabulary.